Incidence of acute kidney injury following cardiac catheterization prior to cardiopulmonary bypass in children. Issue 4 (4th February 2014) - Huggins, Nicholas; Nugent, Alan; Modem, Vinai; Rodriguez, Joseph S.; Forbess, Joseph; Scott, William; Dimas, V. Vivian
<x xml:space="preserve">Abstract</x> Objectives To determine whether contrast administration was a risk factor for development of acute kidney injury (AKI) in cyanotic congenital heart disease (CHD) patients undergoing cardiopulmonary bypass (CPB). Background AKI following CPB or contrast administration is well described. In previous studies, administration of contrast prior to CPB has been shown to increase the risk of AKI. Chronic cyanosis leads to glomerular damage and dysfunction, thus potentially placing this population at increased risk of developing AKI following contrast administration prior to CPB. Methods One hundred twenty‐two patients with cyanotic CHD undergoing preoperative cardiac catheterization (PCC) and subsequent CPB at Children's Medical Center of Dallas from January 1, 2007 until November 30, 2010 were identified, looking specifically at bi‐directional Glenn (BDG) anastomoses and Fontan procedures. One hundred thirteen patients undergoing PCC ≤ 48 hr prior to and > 5 days prior to CPB were included. Occurrence of AKI following CPB was the primary outcome variable. Results Logistic regression analysis revealed pre‐catheterization serum creatinine was a risk factor for post‐CPB AKI (P < 0.001) in both Fontan and BDG patients. All other variables were not significantly associated with the development of AKI in either BDG or Fontan patients. Length of stay (hospital or ICU) was not different among the groups regardless of the occurrence of AKI. Conclusions In this study of cyanotic CHD patients, contrast administration within 48 hr prior to CPB was not an additional risk factor for the development of AKI. © 2014 Wiley Periodicals, Inc.